2013
DOI: 10.2478/aoa-2013-0061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Binaural Stimulation on Attention and EEG

Abstract: When two pure tones of slightly different frequency are presented separately to each ear, the listener perceives a third single tone with amplitude variations at a frequency that equals the difference between the two tones; this perceptual illusion is known as the binaural auditory beat (BB). There are anecdotal reports that suggest that the binaural beat can entrain EEG activity and may affect the arousal levels, although few studies have been published.There is a need for double-blind, well-designed studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 12 publications
4
31
0
1
Order By: Relevance
“…The absence of effects of MB and BB on the quality of attention in the present study is also in line with previous studies which examined the relationship between ABS and attention (Crespo et al, 2013;Kennel, Taylor, Lyon, & Bourguignon, 2010). In these studies, no significant improvement was found in attention performance with BB stimulation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The absence of effects of MB and BB on the quality of attention in the present study is also in line with previous studies which examined the relationship between ABS and attention (Crespo et al, 2013;Kennel, Taylor, Lyon, & Bourguignon, 2010). In these studies, no significant improvement was found in attention performance with BB stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…In a more recent study, high frequency (40 Hz) BBs were presented to 36 students (22 female, 14 male; aged 18-28 years old) and it was shown that the presentation of these BBs increased attentional focusing (Colzato et al, 2017). In contrast, in a placebo controlled study in healthy adults, no significant differences were found between the BB group and control group on any of the presented attention tasks (Crespo, Recuero, Galvez, & Begona, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…The websites marketing digital drugs promote them using some arguments and false claims, such as that they do not contain chemicals, and that they do not affect the body (Curtis & Wendel, 2014). They are also promoted as they make their users feel relaxation or excessive movement and energy (Crespo, Recuero, Galvez, & Begona, 2016), awakening inert memory (Kennel, Taylor, Lyon, Bourguignon, 2014), sense of happiness, imagination and inspiration, all without alcohol or headache. ( Connolly, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies also show that digital drugs affect the level of awakening and concentration of abuser. They affect the normal development of the nervous system among children and young people up to the age of 25 years (Crespo, Recuero, Galvez, & Begona, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation